Nanotechnology Applications in Neuroscience: Advances, Opportunities and Challenges - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2012)
New treatment and prophylaxis needs, which have emerged as the incidence of central nervous system disorders (CNSDs) has increased, have brought two concepts together: neuroscience and nanotechology. Because of the restricton of the blood-brain barrier (BBB), conventional drug delivery systems do not always work to provide the levels of drug molecules to the CNS that are needed for the recovery from CNSDs. Nanotechnology products may provide increased compliance, enhanced bioavailability, better BBB penetration of drug molecules, and a minimized side effect profile. This review considers some important application examples of nanotechnology and micro-electromechanical systems in neuroscience, and drug delivery approaches across the BBB. The major controversies concerninginvasive procedures for application of some products and the use of microchips and nanodevices are also discussed.
Keywords: Neuroscience; central nervous system disorders; blood-brain barrier; nanotechnology; micro-electromechanical systems; ROTIGOTINE TRANSDERMAL PATCH; NANOPARTICLE; ALZHEIMERS; MANAGEMENT; THERAPIES